PREVENTING HIV INFECTION IN PREGNANT WOMEN - Saidolim Murodkosimov; Ermanov Rustam Temirovich; Mamirov Asamidin Egamberdievich; Mamatkulov Talat Toirovich; Samiboeva Umida Khudshidovna (Scholar Express Journals, 2022)
The article examines the epidemiological situation of HIV infection in Samarkand region, outlines the regulatory documents on prevention of HIV infection and the necessary preventive measures for pregnant women. In our country, special attention is paid to measures to counter the spread of HIV infection. In the context of the ongoing epidemic, it is difficult to overestimate the importance of preventive measures, particularly the involvement of the population in HIV testing, including women, who are one of the key groups determining the epidemic spread of HIV infection in our country.
Keywords: AIDS; HIV infection; introspection; prevention of HIV infection; epidemiology of HIV infection